Research Published in "Management International Review" from 2006 to 2020: A Bibliometric Analysis and Future Directions - Mukherjee, Debmalya; Kumar, Satish; Donthu, Naveen; Pandey, Nitesh (Management international review, 2021)
The Management International Review (MIR) celebrated its 60th anniversary in 2020. In commemoration of this event, we use a bibliometric analysis to present a retrospective on the journal by analyzing its content for the years between 2006 and 2020. We find that the collaboration culture in MIR has risen over time with the increase in the median size of author teams. Moreover, the collaboration network has become more global over time. The methodology used in the journal is predominantly empirical and quantitative with archival data sources most commonly used. The bibliographic coupling of the MIR corpus reveals that the major themes in the journal revolve around "culture," "emerging economies," "innovation, knowledge transfer, and absorptive capacity," "internationalization process," "culture and entry modes," and "internationalization and performance." A comparison with other leading international business journals provides distinct pathways in which MIR may continue to grow. Finally, it is important to note that while the share of conceptual studies has decreased significantly in the last 15 years, the MIR editors want to see more novel and theoretically grounded conceptual articles in the journal.